Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan PT. Radio Panjalu Raya - Ellen Erizka; Ustadus Sholihin; Zulfia Rahmawati (Manajemen Kreatif Jurnal, 2023)
This research aims to determine the influence of leadership style variables (X1) and organizational culture (X2) on employee performance (Y) at PT Radio Panjalu Raya. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. The data collection techniques used are primary data and secondary data. Sample selection used the saturated sampling method, the number of samples in the study was 40 respondents at PT Radio Panjalu Raya. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y = 10.743 + 0.269 Organizational culture has a partially significant effect on employee performance with a sig result of 0.000 <0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that leadership style and organizational culture have a simultaneous and significant effect on the performance of PT Radio Panjalu Raya employees.